2013
DOI: 10.1111/ene.12321
|View full text |Cite
|
Sign up to set email alerts
|

Greater occipital nerve blocks in chronic cluster headache: a prospective open‐label study

Abstract: GONB seems to be an efficacious treatment with reproducible effects in CCH patients. Performed three monthly, GONB may have a useful role in the management of CCH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 11 publications
3
81
0
1
Order By: Relevance
“…15,19,40 In one study evaluating service members evacuated from Operations Iraqi and Enduring Freedom with headaches, 4.9% were given a primary diagnosis of ON. 15 However, these statistics may belie the socioeconomic burden of conditions that may respond to interventions targeting the occipital nerve(s), as approximately 50% of migraineurs, 2,5,6,11,23,48 a majority of individuals with cluster headache, 2,4,23,37,45 and significant proportions of individuals with tension-type, 8,48 posttraumatic, 29,48 and cervicogenic headaches 8,23,29 also respond to occipital nerve block.…”
Section: Introductionmentioning
confidence: 99%
“…15,19,40 In one study evaluating service members evacuated from Operations Iraqi and Enduring Freedom with headaches, 4.9% were given a primary diagnosis of ON. 15 However, these statistics may belie the socioeconomic burden of conditions that may respond to interventions targeting the occipital nerve(s), as approximately 50% of migraineurs, 2,5,6,11,23,48 a majority of individuals with cluster headache, 2,4,23,37,45 and significant proportions of individuals with tension-type, 8,48 posttraumatic, 29,48 and cervicogenic headaches 8,23,29 also respond to occipital nerve block.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, afferent nerve blockade such as anaesthesia of the greater occipital nerve has been proposed to reduce nociceptive input and hence headache and has been used with equivocal success in primary headaches [47, 48] but is recently used as a therapeutic option in refractory headache [49], cluster headache [50] and chronic migraine [51]. This concept is supported by clinical experiences and therapeutic efforts in tension-type headache and other primary headaches, which aim at decreasing muscle tension and nociceptive input from pericranial muscles [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…90 As in the previous study, response time was brisk for the corticosteroid group. A more recent open-label study 91 showed that the duration of response was 3 weeks.…”
Section: Occipital Nerve Blocksmentioning
confidence: 99%